2022
DOI: 10.3390/cancers14194576
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Prognostic Features in Patients with Immunotherapy-Induced Vitiligo-like Depigmentation: A Monocentric Prospective Observational Study

Abstract: Vitiligo-like depigmentation (VLD) is an immune-related adverse event (irAE) of checkpoint-inhibitor (CPI) treatment, which has previously been associated with a favourable outcome. The aim of this study was to explore clinical, biological and prognostic features of melanoma patients with VLD under CPI-treatment and to explore whether they exhibit a characteristic immune response profile in peripheral blood. Melanoma patients developing VLD under CPI were included in a prospective observational single-center c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…These cases are not captured in our analysis, as pruritus alone is not formally a rash and macroscopically unchanged skin would very rarely be biopsied. Furthermore, vitiligo-like depigmentation is described as an on-target effect in patients with melanoma in general and frequently with ICB [ 15 ]. However, we did not include this well-characterized adverse event in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cases are not captured in our analysis, as pruritus alone is not formally a rash and macroscopically unchanged skin would very rarely be biopsied. Furthermore, vitiligo-like depigmentation is described as an on-target effect in patients with melanoma in general and frequently with ICB [ 15 ]. However, we did not include this well-characterized adverse event in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vitiligo-like depigmentation and alopecia were not considered for this investigation. Vitiligo-like depigmentations have previously been described [ 15 ], and alopecia is not conventionally considered a skin AE. In addition, vitiligo does not require a biopsy for diagnostic purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are typically characterized by a bilateral and symmetrical distribution pattern, with mostly smaller "freckle-like" macules, with a preferential distribution in ultraviolet-exposed areas (such as the face, hair, and hands), and with a median onset time of approximately 5 months. Melanoma patients with previous targeted therapy (with BRAF and MEK inhibitors) experience a significantly longer time lapse between ICI initiation and VLL onset compared to non-pretreated patients (12.5 vs. 6.2 months) [34,35]. Cytotoxic Tlymphocyte antigen-4 (CTLA4) inhibitor-induced VLLs were less frequent than they were with anti-PD-(L)1 treatment [19], although the combination of anti-PD-(L)1 and anti-CTLA4 usually results in a higher incidence of VLLs [9,19,36].…”
Section: Ici-induced Vllsmentioning
confidence: 99%
“…VLD is strongly associated with improved overall survival and progression-free survival, independent of other prognostic factors [ 14 ]. Hermann et al, 2022 observed that the upregulation of EDAR and downregulation of LAG3 was seen in responders amongst melanoma patients with VLD [ 15 ].…”
mentioning
confidence: 99%